Diversity and Abundance of Macrozoobenthos in the Coastal of Puteri Sidokelar Lamongan - Alif, Trisnani (Science Education and Application Journal, 2021)
Diversity and abundance of macrozoobentos in Puteri Beach Sidokelar Lamongan. Macrozoobenthos are organisms that live on the bottom of waters, and are part of the food chain whose existence depends on the population of organisms at lower levels. This study aims to analyze the diversity of macrozoobenthos found on the coast of Puteri, Sidokelar Village, Lamongan Regency. Macrozoobenthic sampling using the transect method measuring 5 mx 5 m. The identification of this sample was carried out at the Biology Laboratory. Billfath University Lamongan using journaÂ  literature. The results of the study found 5 types of animals consisting of 4 types from the gastropod class 1 type from the class Bivalvia. Types of Cerithidea cingulata were the most common, with as many as 20 individuals. The least type was Gafrarium pectinatum which was found only in 1 individual. Diversity index (H ') in a moderate coastal ecosystem. The community is in a state of moderate stability or diversity with the number of individuals for each species is not uniform but no one is dominant (1 <H '<3).